The Influence of Mother Characteristics on Giving Tempe Broth as an Effort Prevention of Stunting in Toddler - Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani (Universitas Teuku Umar, 2019)
Stunting is one of the effects of nutritional problems from past intake caused by a lack of macro and micro nutrient intake (such as protein, vitamin A, zinc), as well as the frequency of infectious diseases such as diarrhea and low birth weight. Kuala Pesisir sub-district has a prevalence of stunting in 2017 that is 39.2%. Purwodadi Village accounts for the highest stunting case, with 66 toddlers with stunting. The purpose of this study was to determine the effect of mothers' knowledge and attitudes on the provision of tempe broth as an effort to prevent stunting in infants in Purwodadi Village, Kuala Pesisir District, Nagan Raya Regency. This study uses a cross-sectional design with a population of 75 mothers who come from poor families and have toddlers, sampling using a total sampling technique that is as many as 75 mothers who come from misikin families. Data were analyzed by univariate, bivariate, and multivariate using multiple linear regression tests.The results showed a relationship between mother's knowledge and attitude towards the provision of tempe broth as an effort to prevent stunting in infants (P. Value <0.05). For the results of multivariate analysis shows that the mother's knowledge gives a stronger influence on the administration of tempe broth (Ex. B. 27, 28). The conclusion there is a very significant relationship between mother's knowledge and attitude towards the provision of tempe broth. Mother's knowledge gives a stronger influence on the provision of tempe broth as an effort to prevent stunting in infants. It is necessary to increase the education program for the community about the importance of nutrition in preventing stunting in infants.